Parâmetros eletrocardiográficos e valores séricos e urinários de sódio e potássio em cães tratados com furosemida - Pereira, JDG; Camacho, A. A.; Santana, A. E.; Carvalho, M. B. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1998)
The serum and urine Na+ and K+ levels and their relationship with electrocardiography characteristics,were studied in 15 male adult mongrel dogs, treated twice-a-day,with 2, 4, 8mg/kg of live weight doses of furosemide and furosemide associated with KCl during 35 days. Urine samples were analyzed weekly in order to determine the Na+ and K+ concentrations and to evaluate the urinary excretion of both cations. Electrocardiography was performed simultaneously, using limb derivations, speed 50mm/sec and calibration of 1 cm corresponding to 1mV. Data showed decreased seric concentrations of Na+ and Ki, increase in Na+ fractional excretion between days 7 and 21 of the treatment, slower heart rate and longer PR, QRS and QT intervals in the ECG. Briefly 2mg/kg furosemide associated with KCl was the most suitable treatment since it induced lesser side effects.
Seric and urinary values for sodium and potassium and electrocardiography parameters in dogs treated with furosemide
Keywords: dog; electrocardiography; potassium; sodium; furosemide